Pendidikan Kesehatan Pencegahan Kanker Serviks Melalui Media Sosial Bagi Perempuan di Depok, Indonesia - Agustini Liviana Dwi Rahmawati; Dana Prayoga Irawan; Iba Supra Saba; Gusrina Komara Putri; Haslindar Hatta (Karya Kesehatan Journal of Community Engagement, 2026)
Cervical cancer remains a preventable women’s reproductive health issue through increased knowledge, early detection, HPV vaccination, and access to credible health information. Social media has the potential to serve as a health promotion tool because it is easily accessible and widely used by the public. This community service activity aims to improve women’s knowledge about cervical cancer and introduce the use of social media as a reliable source of reproductive health information. The activity was conducted in Kemirimuka Urban Village, Beji Subdistrict, Depok City, West Java, involving 30 women as participants. The method used was community-based health education with a single-group pre-test and post-test design. The intervention was conducted over five hours through health education sessions, screening of educational videos, interactive discussions, and an introduction to using social media to obtain valid health information. Data were analyzed using the Wilcoxon signed-rank test. Results showed a significant increase in participants’ knowledge regarding cervical cancer following the intervention (Z = -4.115; p < 0.001). However, there were no significant changes in social media usage (Z = -0.769; p = 0.442) or knowledge of cervical cancer prevention (Z = -1.254; p = 0.210). These findings indicate that brief community-based education effectively improves general knowledge about cervical cancer, but is not yet sufficient to change social media usage and specific knowledge regarding prevention. Future programs should be supplemented with ongoing digital reinforcement and more practical prevention materials.